Level of Adaptavity of Polish Families on Emigration in the Netherlands in the perception of children - Marta Czechowska-Bieluga; Barbara Sordyl-Lipnicka (Journal of Modern Science)
Objectives The aim of empirical analyses was to identify the level of the adaptivity of families from a perspective of a child who has found him- or herself in one of the following situations: one parent has migrated, both parents have migrated without taking the child with them, or an entire family has migrated.